2019
DOI: 10.1108/itp-08-2017-0257
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ intention to use and recommend e-participation

Abstract: Purpose-The purpose of this paper is to investigate how citizens' perception of empowerment can influence the intention to use and intention to recommend e-participation. Design/methodology/approach-A research model is evaluated using structural equation modelling. An online survey questionnaire was used to collect data from 210 users of e-participation. Findings-The results show that psychological empowerment influences the intention to use and recommend e-participation. Performance expectancy and facilitatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 83 publications
(118 reference statements)
12
84
0
4
Order By: Relevance
“…This is a departure from the findings which have shown that social influence is a significant predictor of the intention to use e-government services (Bhuasiri et al, 2016;Kurfalı et al, 2017;Lu & Nguyen, 2016;Venkatesh et al, 2003;Zawaideh, 2016). Our findings, however, support studies that showed that social influence does not determine the behavioral intention to use (Jacob & Darmawan, 2019;Mansoori et al, 2018;Naranjo-Zolotov et al, 2019). These contradictory findings on the impact of social influence on the behavioral intention to use as reported in the literature appear to suggest that the social influence (opinions/views/ experiences) from friends and family may not necessarily lead to the adoption of e-government services.…”
Section: Discussionsupporting
confidence: 67%
“…This is a departure from the findings which have shown that social influence is a significant predictor of the intention to use e-government services (Bhuasiri et al, 2016;Kurfalı et al, 2017;Lu & Nguyen, 2016;Venkatesh et al, 2003;Zawaideh, 2016). Our findings, however, support studies that showed that social influence does not determine the behavioral intention to use (Jacob & Darmawan, 2019;Mansoori et al, 2018;Naranjo-Zolotov et al, 2019). These contradictory findings on the impact of social influence on the behavioral intention to use as reported in the literature appear to suggest that the social influence (opinions/views/ experiences) from friends and family may not necessarily lead to the adoption of e-government services.…”
Section: Discussionsupporting
confidence: 67%
“…This may reflect the fact that it is easier for the hosts’ friends and acquaintances to control and enforce social norms, as there is less spatial distance between them. In a recent study that tested the UTAUT model, Naranjo-Zolotov, Oliveira, and Casteleyn (2019) found that social norms had an insignificant effect on behavioral intention. The voluntary nature of the use of specific technologies reduces the importance of social influences.…”
Section: Contribution To Researchmentioning
confidence: 99%
“…The United Nations e-Government Survey 2014 report [29] describes a three-level e-Participation model: e-Information, e-Consultation and e-Decision-making. There is a progressive move from a more "passive" role linked to information access and transparency to a more "active" one based on deliberation, decision-making and co-creation [30]. Similarly, Macintosh [10] also pointed to three levels of e-Participation: e-Enabling, e-Engaging and e-Empowering, going from a more passive role for citizens to active involvement that to some extent returns sovereignty to citizens.…”
Section: E-participation Systems: Technological Background and Relatementioning
confidence: 99%
“…Before progressing to more technical issues, we would like to stress that, from the perspective of the literature on e-Participation, the inclusion of rights as a way of recognizing participation in a process is intended as a means of addressing a fundamental problem in direct democracy: the lack of the motivation to participate in certain cases [51]. As Naranjo-Zolotov et al [30] stated, a decision-making-based participation model requires "an active engagement and involvement of the citizens in the long-term scenario for its success". Edelmann et al [52] posed the question in other terms: "Given that lurkers make up a majority in the e-participation process, the crucial question is how we can motivate them to become active".…”
Section: E-participation Systems: Technological Background and Relatementioning
confidence: 99%